Peculiarities of Implementation of the Environmental Management System of Motor Transport Enterprises on the Urban Territories - KHRUTBA, Viktoriia O.; KUPALOVA, Galyna I.; ZIUZIUN, Vadym I.; NIKITCHENKO, Yuliia S.; KOLOMIIETS, Serhii V. (Journal of Environmental Management and Tourism, 2019)
It has been found out that the environment management system (EMS) in accordance with the standards of ISO 14001: 2015 is a universal instrument for ensuring the sustainable development of the transport system, the activity of transport enterprises, and reducing their environmental impact on the territory of modern cities. It has been determined that transport in cities is the main source of environmental and physical hazards. The realization of a full-scale experiment for a typical automobile enterprise allowed conducting a preliminary environmental analysis of the activity. For the implementation of environmental management for the transport company, a process model is proposed that defines the sequence of actions and includes the main processes that ensure the implementation of the Deming-Shuhart cycle. Based on the model, elements of the ecological management system and the typical procedures of the EMS implementation processes have been developed. The defining procedure is the proposed environmental policy of the motor transport company, which is the basis for its further activities. A register of essential environmental aspects has been developed, an action plan has been developed, which sets out the goals and objectives for the gradual maintenance of an effective system of environmental management.